The Effect of Substitution of Soy Tempe Flour and Mung Bean Flour on Biscuits PMT for Stunting in Aged 6 – 59 Months - Khofifah, Nur Aini; Razak, Maryam; Pudjirahaju, Astutik (Politeknik Kesehatan Kemenkes Malang, 2023)
Background: The 2018 Basic Health Research reports that the national prevalence of stunting has decreased to 30.8%. However, the figure of 30.8% is above the 2015-2019 RPJM. Furthermore, the prevalence of stunting in Malang Regency and Malang City in 2021 is 25.7%. The 25.7% figure is still above the 2020-2024 Public Health Program Action Plan which targets stunting at 14%. Lack of food intake and infectious diseases are the direct causes of stunting in toddlers. The government program to overcome the handling of stunting in toddlers is by doing PMT. Modified PMT using local food ingredients is very effective in improving the nutritional status of toddlers who are stunted. One of the local food ingredients with high nutritional value is soy tempe and mung beans. Objective: To analyze the effect of substitution of soy tempe flour and mung bean flour on the chemical quality, nutritional quality and organoleptic quality of biscuits as PMT for preventing stunting in children aged 6 – 59 months. Methods: Experimental with 4 treatment levels and 3 repetitions in the analysis of chemical quality, nutritional quality, and organoleptic quality. Results: The lower the proportion of soy tempe flour, the lower the protein, fat and energy value and the higher the proportion of mung bean flour, the higher the carbohydrate content. Conclusion: Calculation of the calculated value of the best treatment level is P2 (50:20:30). PMT Biscuits Substitute Soy Tempe Flour and Mung Bean Flour for Stunting Toddlers have a significant effect on color, aroma, taste and texture.